2017
DOI: 10.1002/ijc.30887
|View full text |Cite
|
Sign up to set email alerts
|

Detailed longitudinal sampling of glioma stem cells in situ reveals Chr7 gain and Chr10 loss as repeated events in primary tumor formation and recurrence

Abstract: Intratumoral heterogeneity at the genetic, epigenetic, transcriptomic, and morphologic levels is a commonly observed phenomenon in many aggressive cancer types. Clonal evolution during tumor formation and in response to therapeutic intervention can be predicted utilizing reverse engineering approaches on detailed genomic snapshots of heterogeneous patient tumor samples. In this study, we developed an extensive dataset for a GBM case via the generation of polyclonal and monoclonal glioma stem cell lines from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The median overall survival (OS) of patients with glioblastoma (GBM; WHO grade IV) is only approximately 15 months (1,3,4). Patients with lower-grade diffuse glioma (LGG, WHO grade II/III) have a relatively favorable prognosis, but these tumors evolve and most relapse as therapy-resistant higher-grade gliomas over time (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The median overall survival (OS) of patients with glioblastoma (GBM; WHO grade IV) is only approximately 15 months (1,3,4). Patients with lower-grade diffuse glioma (LGG, WHO grade II/III) have a relatively favorable prognosis, but these tumors evolve and most relapse as therapy-resistant higher-grade gliomas over time (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…We also identified that the up-regulation of ETV1, an important oncogene involved in transcriptional regulatory processes in GBMs [112], was due to a chromosome 7 gain in AHOL1 genome. It has been shown that chromosome 7 gain is a key event in G-CIMP-negative GBMs [23,113], and high expression of ETV1 may be a potential downstream effector of chromosome 7 gain [112]. Previous study also revealed that ETV1 is fused with DGKB and may act as oncogenic drivers in pediatric high-grade gliomas [114].…”
Section: Gene Expression Validation Of the Microarray Resultsmentioning
confidence: 88%
“…Suppressing the apoptotic potential through gene expression regulation in the irradiated cells was a proposed mechanism that explained the radioresistant nature of the irradiated GBM cells [ 107 , 108 ]. Many apoptotic genes discovered in our study were known to play major roles in attenuating GBM apoptosis, especially, BBC3 , DCC , BEX2 , CASP1 , IL1B , and SFRP2 [ 115 , 116 , 117 , 118 , 119 , 120 ]. GBM cells produce an immunosuppressive microenvironment to escape immune surveillance and enhance their own survival, and this can be accomplished through the secretion of transforming growth factor β ( TGF-β ) to block T cell activation and proliferation [ 121 ].…”
Section: Identification Of Novel Drug Targets To Combat Radioresimentioning
confidence: 99%